Injury characteristics in women in relation to their menopausal status - Timler, Dariusz; Bogusiak, Katarzyna; Kasielska-Trojan, Anna; Madziała, Marcin; Szarpak, Łukasz (Menopause Review/Przegląd Menopauzalny, 2013)
Aim of the study: Analysis of the frequency and characteristics of injuries in women depending on their menopausal status. Material and methods: The retrospective study included 1362 women treated in the Copernicus Memorial Hospital in Lodz in 2011 because of the injury. The population was divided according to the menopausal status: women of the reproductive age (group I), women in the peri-menopausal period (group II) and postmenopausal women (group III). The analysis included the time of injury, its type and cause, duration of hospitalization, and mortality. Results: The most common trauma in the examined women were head injuries. The groups differed in terms of the causes of injury. Postmenopausal women were hospitalized significantly longer than women in the reproductive age (p < 0.001) and in the peri-menopausal period (p < 0.001). They were also characterized by the highest mortality. Conclusions: The physiological changes in women’s body, related to their menopausal status are reflected in the characteristics of injuries occurring in different periods of life. Differences in trauma causes were observed – in women of the reproductive age, the most common causes were traffic accidents while in those in peri- and postmenopausal periods – same-level falls. It may be associated with the fact that in peri- and postmenopausal women falls may result in low-energy osteoporotic fractures needing hospitalization.